Calcifying Phytoplankton Demonstrate an Enhanced Role in Greenhouse Atmospheric CO2 Regulation - Kvale, Karin; Koeve, Wolfgang; Mengis, Nadine (Frontiers in Marine Science, 2021)
The impact of calcifying phytoplankton on atmospheric CO2 concentration is determined by a number of factors, including their degree of ecological success as well as the buffering capacity of the ocean/marine sediment system. The relative importance of these factors has changed over Earth's history and this has implications for atmospheric CO2 and climate regulation. We explore some of these implications with four ``Strangelove'' experiments: two in which soft-tissue production and calcification is stopped, and two in which only calcite production is forced to stop, in idealized icehouse and greenhouse climates. We find that in the icehouse climate the loss of calcifiers compensates the atmospheric CO2 impact of the loss of all phytoplankton by roughly one-sixth (with the resulting maximum rise of CO2, 146 ppm, due to the loss of both biological pumps about 6 times larger than the corresponding loss of CO2, 21 ppm, due to the stoppage of the carbonate counter-pump). But in the greenhouse climate the loss of calcifiers compensates the loss of all phytoplankton by about half with the resulting rise of CO2, 252 ppm, due to the loss of both biological pumps only slightly more than the resulting loss of CO2, 236 ppm, due to the stoppage of only the carbonate counter-pump). This increased impact on atmospheric CO2 concentration is due to the combination of higher rates of pelagic calcification due to warmer temperatures and weaker buffering due to widespread acidification in the greenhouse ocean. However, the greenhouse atmospheric temperature response per unit of CO2 change to removing ocean soft-tissue production and calcification is only one-fourth that in an icehouse climate, owing to the logarithmic radiative forcing dependency on atmospheric CO2 thereby reducing the climate feedback of mass extinction. This decoupling of carbon cycle and temperature sensitivities offers a mechanism to explain the dichotomy of both enhanced climate stability and destabilisation of the carbonate compensation depth in greenhouse climates.